Property law as a barrier to energy upgrades in multi-owned properties: insights from a study of England and Scotland - Weatherall, D; McCarthy, F; Bright, S (Springer Verlag, 2017)
Is the law of ownership a barrier to energy upgrades in apartment blocks? Co-owners in multi-owned properties face challenges in reaching agreement to implement energy efficiency measures that owners of single family residences do not encounter. At the European level, this difficulty is recognised in Article 19 of the 2012 Energy Efficiency Directive, by which governments are obliged to address barriers to improvements which arise in the specific context of multi-owner properties. Despite this, the position of apartment owners remains mostly invisible in the policy discourse. The small quantity of literature examining the difficulties of group decision making around energy efficiency in apartments has so far focused on mapping the issues. This paper begins the process of ‘colouring in’ the existing outlines by providing an in-depth delineation of the governance barriers to energy upgrades presented by the law of ownership and management in two European jurisdictions: England and Scotland. A doctrinal analysis is employed to ascertain the relevant legal issues and identify how property law constitutes a barrier to energy upgrades within the framework of existing behavioural models. A theoretical inquiry is then used to suggest that reconceptualising property law in the context of multi-owner properties to focus on collective responsibilities rather than individual rights may help to minimise this effect of the law. The paper concludes with recommendations for further research to identify the range of issues property law presents across EU member states. This data is needed to fully test the reconceptualisation hypothesis presented here.